Online discussion and the 2014 Scottish independence referendum: Flaming keyboards or forums for deliberation?. (June 2015) - Quinlan, Stephen; Shephard, Mark; Paterson, Lindsay
Abstract: Referendums often fail to live up to a deliberative standard, with many characterised by low levels of knowledge, disinterest and misinformation, negativity, and a focus on extraneous issues to which voters are voting. But social media offers new avenues for referendums to incorporate a greater deliberative dimension. Through a content analysis of BBC discussion forums, we test whether online discussion of the Scottish independence referendum has deliberative characteristics. Results suggest a mixed picture with conversation displaying some deliberative features (low incidences of flaming/discussion of referendum issues). However, low levels of discussion intensity, dominance by a few, little knowledge exchange, and high gender inequality illustrate that online referendum discussion lacks deliberative characteristics, implying that social media are not a panacea for referendum deliberation.